“Virtual unreality”: unreal augmentation of perception and action must fit the task to be beneficial - Neuhaus, Robin; Ringfort-Felner, Ronda; Feitsch, Jochen; Kempken, Gabriel; Dakhane, Sarvesh; Hassenzahl, Marc (Frontiers in Virtual Reality, 2025)
“Unreal” augmentations of perception and action (e.g., looking through walls, flying) represent a distinctive design opportunity in Virtual Reality (VR), allowing users to transcend real-world limitations. Yet the conditions under which such augmentations yield positive experience remain unclear. In this study, we tested whether the experience of being augmented depends on compatibility with the given task. In a between-subject experimental vignette study (N = 120 experienced VR users), participants watched first-person videos in one of three conditions: (1) reality-oriented object manipulation (control), (2) task-compatible augmentation (growing/shrinking), or (3) non-task-compatible augmentation (distant grasping). As expected, the augmentation-oriented design only led to a greater sense of augmentation when it was compatible with the task. In turn, the experience of augmentation was positively related to positive affect, need fulfillment, and hedonic quality. These findings suggest that unreal augmentations are beneficial, but only when the new abilities match the task.